(untitled) (Homoeopathy for All, 2025)
Adenomyosis is a medical condition characterized by the presence of endometrial tissue within the muscular wall of the uterus, leading to various debilitating symptoms such as heavy menstrual bleeding, pelvic pain, and discomfort. This condition poses significant challenges in conventional treatment, prompting an exploration of alternative therapies, including homoeopathy.